Improvement of Mathematical Communication Skills for Students DIII Mechanical Engineering with Think Pair Share Method: A Case of Indonesia - M. Taufik Qurohman; Syaefani Arif Romadhon; Muchamad Sobri Sungkar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2021)
Think Pair Share (TPS) based on Mathematical Good communication is a good thing expected related to the solutions students in college to improve the attractiveness and troubleshooting ability for mechanical engineering students in Indonesia. Research on this occasion is CAR (Class Action Research) . Results of the study are: (1) student interest before and after learning undergoes a change in the first cycle that 53% experienced an increase in 97% at cycle stage II, (2) there is an increase in in a student learning process activity that can be viewed from percentage level to student activities in the first phase cycle 83% which have a fairly active conclusion, and in the next cycle with 100%, (3) in this study there was an increase in the value of student achievement from has an average score of achieved from students in this early cycle 68 with the completeness of student learning in this study by 53% and in the second cycle 94 with 97% student learning completeness.